Franks, Romans, and the emergence of the Merovingian Dynasty in Gaul: a case study of King Childeric (5th Century) - Vaz Stein, Anderson Leonardo (Romanitas - Revista de Estudos Grecolatinos, 2026)
This article presents a case study on the formation of the Merovingian Frankish kingdom in Gaul during the fifth century through an analysis of evidence related to King Childeric I, who died in 481. To this end, it draws on a body of documentary material composed of written sources, mostly dating from the sixth century, as well as archaeological data associated with the burial ceremony of the aforementioned monarch. The analysis of this evidence, considered together with the historiography, reconstructs Childeric as a ruler operating amid both Roman and Germanic influences, responsible for the formation of a kingdom based in Belgica Secunda through conflicts and cooperation with local forces and the Roman Empire. On the other hand, his richly adorned burial ceremony, modeled on those of Germanic leaders, suggests that the legitimacy of his rule and that of his successor was grounded in the display of a warrior authority rooted in a non-Roman tradition.
Keywords: Merovingian Kingdom; Childeric; Ethnogenesis